Role of Notch signaling pathway in gastric cancer pathogenesis - Brzozowa, Marlena; Mielańczyk, Łukasz; Michalski, Marek; Malinowski, Łukasz; Kowalczyk-Ziomek, Grażyna; Helewski, Krzysztof; Harabin-Słowińska, Marzena; Wojnicz, Romuald (Contemporary Oncology/Współczesna Onkologia, 2013)
Notch signaling pathway is activated dynamically during evolution playing significant role in cell fate determination and differentiation. It has been known that alterations of this pathway may lead to human malignancies, including gastric cancer. Despite a decline in the overall incidence, this disease still remains an important global health problem. Therefore, a better understanding of the molecular alterations underlying gastric cancer may contribute to the development of rationally designed molecular targeted therapies. It has been reported that Notch1 receptor could become a prognostic marker of gastric cancer and novel target for gastric cancer therapy. Among the novel and targeted approaches for the treatment of gastric cancer is also the process of Notch receptors regulation by specific microRNA. γ-secretase inhibitors are also taken into consideration.